Experimental investigation on hard rock fragmentation of inserted tooth cutter using a newly designed indentation testing apparatus - Zou, Jiuqun; Yang, Weihao; Zhang, Tao; Wang, Xiaofei; Gao, Min (International journal of mining science and technology, 2022)
This investigation aims to explore the effects of stress conditions and rock cutting rates on hard rock fragmentation through indentation tests on a newly designed triaxial testing apparatus. This apparatus was designed to realize a triaxial loading and indentation test of cylindrical specimens using inserted tooth cutter. The boreability and crushing efficiency of granite rock was investigated by analyzing the change rules of the thrusting force, penetration depth, characteristics of chippings and failure patterns. Several quantitative indexes were used to evaluate rock boreability in this investigation. The granite rock samples all had a chiselled pit and a crushed rock core. Under initial stress conditions, only flat-shape chippings were stripped from the rock surface when the thrusting force reached 20 kN. The rock cutting special energy had a close correlation with the initial stress conditions and inserted tooth shape. Moreover, a thrusting force prediction model was proposed in this paper. The contribution of this study is that for the first time the influence mechanism of the initial triaxial stress conditions on rock fragmentation is investigated using an inserted tooth and the newly designed testing apparatus. This study has a crucial importance for practical underground hard rock crushing in geoengineering.